Early temporomandibular joint disorders due to edentulous spaces in young adults: Study descriptive - Lai, Steven; Damayanti, Lisda; Wulansari, Daisy (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACTIntroduction: Temporomanidbular Disorder (TMD) is a neuromuscular and musculoskeletal disorder that occurs due to disharmony between the components of the stomatognathic system, teeth, and surrounding tissues, so that it can lead to various disorders that are often characterized by pain in the Temporomandibular join (TMJ) and the surrounding complex tissues, namely muscles. nerves, blood vessels, tendons, ligaments, fibrocartilage, and synovial fluid. TMD caused by edentulous spaces in young adults can cause a decrease in a person's quality of life in carrying out daily activities because the temporomandibular joint is part of the stomatognathic system which means it is directly related to the body's work functions and includes the growth and development of the human jaw and face. Knowing the description of temporomandibular joint disorders due to edentulous spaces in young adults. Methods: This type of research is descriptive with cross-sectional method. The research sample was preclinical and clinical students of the Faculty of Dentistry, Padjadjaran University with a total of 45 people obtained using a total sampling technique. Data were collected using a Temporomandibular Disorder-Index Diagnostic (TMD-ID) questionnaire and a questionnaire regarding the presence of edentulous spaces.  Results: Obtained a total of 45 samples consisting of 13 males (27.95%) and 32 females (72.05%). Based on the classification of temporomandibular joint disorders due to edentulous space, it resulted in two categories, namely positive TMD consisting of 33 people (73.33%) and negative TMD consisting of 12 people (26.67%). Conclusion: Disorders of the temporomandibular joint due to edentulous spaces in FKG students at Padjadjaran University.KEY WORDS: young adults, temporomandibular joint, edentulous, TMDGangguan sendi temporomandibular akibat ruang edentulous pada usia dewasa mudaABSTRAKPendahuluan: Temporomandibular Disorder (TMD) adalah gangguan yang terjadi pada neuromuskular dan muskuloskeletal yang terjadi akibat disharmoni antara komponen sistem stomatognatik, gigi, dan jaringan di sekitarnya, sehingga dapat mengakibatkan berbagai gangguan yang sering kali ditandai dengan rasa nyeri pada Temporomandibular Join (TMJ) beserta jaringan kompleks disekitarnya. TMD yang disebabkan oleh ruang edentulous pada usia dewasa muda dapat menimbulkan penurunan kualitas hidup seseorang dalam menjalani kegiatan sehari-hari karena sendi temporomandibula merupakan bagian dari sistem stomatognatik yang artinya berhubungan langsung dengan fungsi kerja tubuh dan meliputi tumbuh kembang rahang dan wajah manusia. Tujuan penelitian mengetahui gangguan sendi temporomandibula akibat ruang edentulous pada usia dewasa muda. Metode: Jenis penelitian deskriptif dengan metode cross-sectional. Sampel penelitian adalah mahasiswa preklinik dan klinik Fakultas Kedokteran Gigi Universitas Padjadjaran dengan jumlah 45 orang yang diperoleh menggunakan teknik total sampling. Pengambilan data dilakukan menggunakan kuesioner Temporomandibular Disorder–Index Diagnostic (TMD-ID) dan kuesioner mengenai ruang edentulous. Hasil: Didapatkan jumlah total 45 sampel yang terdiri dari 13 laki-laki (27,95%) dan 32 perempuan (72,05%). Berdasarkan pembagian kategori gangguan sendi temporomandibula akibat ruang edentulous, menghasilkan dua kategori, yaitu TMD positif yang terdiri dari 33 orang (73,33%) dan TMD negatif yang terdiri dari 12 orang (26,67%). Simpulan: Gangguan sendi temporomandibula akibat ruang edentulous pada mahasiswa FKG Universitas Padjadjaran adalah tinggi.KATA KUNCI: dewasa muda, gangguan, sendi temporomandibular, edentulous, TMD.